The Vitalness of Negative and Positive Freedom on Kathy Hoyle’s Breathe - Wardhana, Bima Tri; Fatiha, Kayla; Kartika, Ratih; Hamidah, Galuh Fadhelah Aulia; Pasopati, Rommel Utungga; Andharu, Devito; Fadillah, Muhammad Reza Ishadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article investigates tensions of positive and negative freedom in a flash fiction of Kathy Hoyle entitled Breathe. The story explores themes of personal growth and resilience through one character's struggle. It fits character development in overcoming challenges and emphasizing the importance of inner strength and self-discovery. Through qualitative method and explorative approach, this paper exemplifies negative freedom with the sense of urgencies in positive freedom. The absence of external restraints must also be accompanied with comprehensive senses of belief. In analysis, the protagonist's journey from vulnerability to strength illustrates the human capacity to endure and transform in the face of life's challenges, highlighting resilience and growth in the face of adversity. In conclusion, it reminds people that even in the darkest of times, they still have the strength to breathe, endure, and ultimately thrive towards following positive freedom.